The effect of prophylactic high dose N-acetylcysteine for the prevention of contrast induced AKI in patients with CKD (stage 3 and stage 4) (Journal of Dhaka National Medical College & Hospital, 2018)
Background: Contrast induced acute kidney injury (CI-AKI) is a frequent cause of acute renal dysfunction following intravascular contrast administration. It is more frequent in chronic kidney disease population. High dose N-acetylcysteine (NAC) may provide better prophylaxis against CI-AKI than standard dose in CKD patient. Several measures are taken to prevent CI-AKI including to avoid use of nephrotoxic drugs, using non pharmacological (Iso-osmolar or low osmolar contrast media) and pharmacological (isotonic saline, iv sodium bicarbonate) agent etc.Objective: To assess the effect of high dose N-acetylcysteine on prevention of contrast induced AKI in CKD patient in comparison to standard dose.Method: Total 44 patients undergoing coronary angiogram (CAG) and/or percutaneous coronary intervention (PCI) were randomly selected into two groups. One group received single high dose NAC 1200mg IV bolus before procedure and 1200 mg orally twice daily for the 1st 48 hours after CAG. The Other group received single standard dose NAC 600mg iv bolus and 600 mg orally twice daily for 48 hours after intervention. All patients were hydrated with isotonic saline (0.9%Nacl) up to 500ml starting 3-4 hrs before and continuing after intervention.Results: Contrast induced acute kidney injury (CI-AKI) occurred in 9 % of the total subjects. Four of the 23 patients in standard dose NAC group (17%) developed AKI whereas none is in high dose NAC group developed AKI. In the standard dose NAC group, pre procedure mean serum creatinine was 1.8±0.6 mg/dl which increased to 1.9±0.7 mg/dl at 48 h post procedure (p=0.025). In high dose NAC group, pre procedure mean serum creatinine fall from 1.9±0.5mg/dl to 1.8±0.5 mg/dl at 48 h post procedure (p=0.015).Conclusion: Administration of high dose N-acetylcysteine is more renoprotective using standard dose in reducing contrast induced acute kidney injury (CI-AKI) in patients with CKD (stage 3 and stage 4).J. Dhaka National Med. Coll. Hos. 2018; 24 (01): 11-17